2012
DOI: 10.1103/physrevb.85.035412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elastic deformation on frictional properties of few-layer graphene

Abstract: We describe the results of Brownian dynamics (BD) simulations of an atomic force microscope (AFM) tip scanned on locally suspended few-layer graphene. The effects of surface compliance and sample relaxation are directly related to the observed friction force. We demonstrate that the experimentally observed reduction of friction with an increasing number of graphene layers in case of a narrow scanning tip can be a result of decreased sample deformation energy due to increased local contact stiffness under the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 23 publications
(42 reference statements)
7
93
0
4
Order By: Relevance
“…3 For the non-pre-strained model (υ=0), µ decreased with the increase of k. But for the pre-strained models, µ increased linearly with the increase of k which is not corresponding to the theory of Ref. 25. Meanwhile, 1/k decreased by up to 51% during the pre-strain increased from 0 to 0.12, so it would be less likely to result in a sharp decrease in friction coefficient µ.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…3 For the non-pre-strained model (υ=0), µ decreased with the increase of k. But for the pre-strained models, µ increased linearly with the increase of k which is not corresponding to the theory of Ref. 25. Meanwhile, 1/k decreased by up to 51% during the pre-strain increased from 0 to 0.12, so it would be less likely to result in a sharp decrease in friction coefficient µ.…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that the friction properties of non-strained suspended graphene are mainly affected by elastic deformation energy and thus µ is approximately proportional to the reciprocal of contact stiffness k=F N /δ, 25 whereF N is the vertical load applied on diamond tip and δ is the deflection of the graphene layer. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Friction increases because graphene deformations enhance the real contact area at the tip apex. In this interpretation, the amount of deformation decreases with increasing number of layers, as revealed by computer simulations [109][110][111][112], with the result that friction diminishes for increasing graphene thickness.…”
Section: Layered Materialsmentioning
confidence: 93%